Taking Sides: The Frames of Online Media on the Bilateral Relationship Between Indonesia and Malaysia - GATUT PRIYO WIDODO; INRI INDRAYANI (Jurnal Studi Pemerintahan, 2014)
The relations between Indonesia and Malaysia are always full of dynamics. Indonesia is always known as old brother of Malaysia since it has similar history, religion also socio cultural background. Some decades show that the decline of relationship of both countries. Another time, as ASEAN members, the two countries devote their nationalities to purify their collective identities as Eastern nations. The objective of the research is to extricate the construction of Kompas online and Utusan online toward news coverage of the borders dispute between Indonesia-Malaysia in 2010. This research is proposed to examine central issues which reported by Kompas online and Utusan online consistently. As a media, Kompas coverage dominates circulation nationally. Kompas.com was the pioneer of online news in Indonesia and was born in reformation era. Utusan is a prominent media industry in Malaysia that was conducted by UMNO as the ruling party in Malaysia for some periods. The method used in this research is framing method by Robert N. Entman’s which consists of four steps identification: defining problem, diagnosing causes, moral judgment and a treatment recommendation. This research found that Kompas news covered the border dispute must be negotiated as recognition of Indonesia dignity. On the contrary, Utusan’s spectacle focused on the Indonesian demonstrators anarchism during the dispute. Keywords: Online Media, media construction, the border dispute, Indonesia-Malaysia’s Bilateral Relations